Sclerotic composition and sclerotic product
The curing composition with a specific anion-based dispersant and balanced components addresses powdered blowing and high viscosity issues in TIMs, providing effective thermal conductivity and flexibility in the cured product.
Patent Information
- Application Number
- JP2021061092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Existing gap fillers used in thermal interface materials (TIMs) suffer from powdered blowing after curing, which is the peeling of thermal conductivity fillers from the surface, and they also have high viscosity issues.
A curing composition containing an anion-based dispersant with a specific OH value, a monomer with acryloyl groups, a polymerization starter, a plasticizer, and thermal conductivity fillers, with a balanced ratio of components to enhance dispersibility and maintain low viscosity.
The composition effectively suppresses powdered blowing and maintains low viscosity, ensuring excellent thermal conductivity and flexibility in the cured product, making it suitable for gap fillers.
Smart Images

Figure 0007624340000001 
Figure 0007624340000002 
Figure 0007624340000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to curable compositions and cured products. [Background technology]
[0002] In recent years, the performance of electronic devices such as personal computers, mobile phones, and personal digital assistants (PDAs), and lighting and display devices such as light emitting diodes (LEDs) and electronic luminescent devices (ELs) has improved significantly, which is due to the remarkable improvement in the performance of computing elements and light emitting elements. As the performance of computing elements and light emitting elements improves, the amount of heat generated also increases significantly, and how to dissipate heat in electronic devices, lighting, and display devices has become an important issue. As a heat countermeasure, measures have been taken to provide TIM (Thermal Interface Materials) between the heating element and the heat sink in order to transfer the heat generated by the computing element or light emitting element to the heat sink without loss and dissipate the heat through the heat sink. Commonly used TIMs include heat dissipation sheets, thermally conductive greases, and gap fillers, but gap fillers, which are initially in a paste form and harden into a solid after application, have attracted attention.
[0003] As an example of a gap filler having excellent flexibility, shape stability, and thermal conductivity, Patent Document 1 discloses a curable composition containing a compound (A) having one (meth)acrylate group in one molecule, a compound (B) having two or more (meth)acrylate groups in one molecule, a polymerization initiator (C), a dispersant (D), and a thermally conductive filler (E) containing zinc oxide. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 149193 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of one embodiment of the present disclosure is to provide a curable composition that is excellent in suppressing powdering after curing. Another problem to be solved by another embodiment of the present disclosure is to provide a cured product that is excellent in suppressing powdering. In this specification, "dusting" means peeling of the thermally conductive filler (F) from the surface of the curable composition after curing, and "suppression of dusting" means suppression of peeling of the thermally conductive filler (F) from the surface of the curable composition after curing. [Means for solving the problem]
[0006] Means for solving the above problems include the following embodiments. <1> An anionic dispersant (A) having an OH value of 40 mg KOH to 160 mg KOH / g; A monomer (B) having a (meth)acryloyl group; A polymerization initiator (D), A plasticizer (E); A thermally conductive filler (F); Including, A curable composition, wherein the content of the anionic dispersant (A) is 0.1% by mass to 1.0% by mass relative to the total mass of the composition. <2> The monomer (B) contains a compound represented by the following formula (1): <1> The curable composition according to claim 1.
[0007] [ka]
[0008] In formula (1), R 1 represents an alkyl group having 1 to 50 carbon atoms, R 2 represents a hydrogen atom or a methyl group. <3> The monomer (B) contains a compound represented by the following formula (2): <1> or <2> The curable composition according to claim 1.
[0009] [ka]
[0010] In formula (2), R B1 represents an alkylene group having 1 to 5 carbon atoms, R B2 and R B3 each independently represents a hydrogen atom or a methyl group, and n represents an integer of 4 or greater.
[0011] <4> The anionic dispersant (A) contains an acid group and a salt thereof; <1> ~ <3> 13. The curable composition according to claim 12, <5> the acid group is a carboxy group or a phosphate group; <4> The curable composition according to claim 1. <6> The molecular weight of the anionic dispersant (A) is less than 1,000. <1> ~ <5> 13. The curable composition according to claim 12, <7> The plasticizer (F) contains an acrylic polymer or a trimellitic acid ester. <1> ~ <6> 13. The curable composition according to claim 12, <8> a ratio of the content of the anionic dispersant (A) to the thermally conductive filler (F) (anionic dispersant (A) / thermally conductive filler (F)) is 0.001 to 0.015 on a mass basis; <1> ~ <7> 13. The curable composition according to claim 12, <9> The thermally conductive filler (F) contains zinc oxide. <1> ~ <8> 13. The curable composition according to claim 12, <10> The content of the thermally conductive filler (F) is 70% by mass to 98% by mass based on the total mass of the composition. <1> ~ <9> 13. The curable composition according to claim 12, <11> <1> ~ <10> 2. A cured product of the curable composition according to claim 1. Effect of the Invention
[0012] According to one embodiment of the present disclosure, there is provided a curable composition that is excellent in suppressing powdering after curing. According to another embodiment of the present disclosure, there is provided a cured product that is excellent in suppressing powdering. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments for carrying out the curable composition and the cured product thereof according to the present disclosure will be described in detail. In this disclosure, the term "to" indicating a numerical range indicates a range including the numerical values respectively stated as the upper and lower limits. In addition, when a unit is stated only for the upper limit of a numerical range expressed by "to", it means that the lower limit is also in the same unit. In the present disclosure, the content or amount of each component in a composition means, when multiple substances corresponding to each component are present in the composition, the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, in which numerical ranges are described in stages, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.
[0014] In the present disclosure, "(meth)acrylic" is a term used as a concept that includes both acrylic and methacrylic, and "(meth)acryloyl" is a term used as a concept that includes both acryloyl and methacryloyl. In the present disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. In the present disclosure, when a plurality of components are present in the composition, each component in the composition means the total amount of the corresponding plurality of substances present in the composition, unless otherwise specified. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In this disclosure, "JIS" is used as an abbreviation for Japanese Industrial Standards.
[0015] (Curable composition) The curable composition according to the present disclosure comprises an anionic dispersant (A) having an OH value of 40 mgKOH / g to 160 mgKOH / g, a monomer (B) having a (meth)acryloyl group, a polymerization initiator (D), a plasticizer (E), and a thermally conductive filler (F), and the content of the anionic dispersant (A) is 0.1 mass % to 1.0 mass % with respect to the total mass of the composition. When the curable composition according to the present disclosure has the above-described configuration, it is excellent in suppressing powdering after curing. In this specification, "dusting" means peeling of the thermally conductive filler (F) from the surface of the curable composition after curing, and "suppression of dusting" means suppression of peeling of the thermally conductive filler (F) from the surface of the curable composition after curing.
[0016] Dispersants such as oleic acid and selachyl alcohol contained in the curable composition used in the gap filler have good wettability to the filler and contribute to reducing the viscosity of the composition, but have poor compatibility with components other than the filler (e.g., monomers having a (meth)acryloyl group, plasticizer components, etc.), and therefore tend to cause powdering after curing. For this reason, further improvements are required to prevent powdering of the curable composition used in the gap filler. Therefore, the inventors conducted extensive research and found that, in order to suppress powdering and maintain a low viscosity in a curable composition used as a gap filler, the dispersant needs to have both excellent wettability with respect to the filler and excellent compatibility with components other than the filler, and thus arrived at the configuration of the curable composition according to the present disclosure. Although the detailed mechanism by which the above effects are obtained is unclear, it is speculated as follows.
[0017] The anionic dispersant (A) contained in the curable composition according to the present disclosure has a specific OH value, and therefore has good wettability with the thermally conductive filler (F). Furthermore, since the anionic dispersant (A) is contained in the composition within a specific content range, it is presumed that the compatibility between the thermally conductive filler (F) and the monomer (B) having a (meth)acryloyl group is also improved, and peeling (powdery) of the thermally conductive filler (F) from the surface of the curable composition after curing is effectively suppressed. In addition, since the curable composition according to the present disclosure has an anionic dispersant (A) having a specific OH value and being contained in a specific amount in the composition, it is presumed that the curable composition exhibits optimal dispersibility for the thermally conductive filler, and therefore is also excellent in maintaining the viscosity of the curable composition low (hereinafter also referred to as "low viscosity maintenance"). Hereinafter, each component of the curable composition according to the present disclosure will be described.
[0018] <Anionic dispersant (A)> The curable composition according to the present disclosure contains an anionic dispersant (A) having an OH value of 40 mgKOH / g to 160 mgKOH / g (hereinafter, may be simply referred to as "anionic dispersant (A)"), and the content of the anionic dispersant (A) is 0.1 mass % to 1.0 mass % relative to the total mass of the composition. By including an anionic dispersant (A) having an OH value within the above range in the composition in an amount within the above range, powdering after curing is suppressed and low viscosity is maintained.
[0019] The OH value of the anionic dispersant (A) is the mass (mg) of potassium hydroxide required to neutralize the acid groups (e.g., free fatty acids, resins having acid groups, etc.) contained in 1 g of sample, and is determined by the method described in JIS: K 0070-1992.
[0020] The OH value of the anionic dispersant (A) is preferably from 50 mgKOH / g to 150 mgKOH / g, more preferably from 60 mgKOH / g to 140 mgKOH / g, and even more preferably from 65 mgKOH / g to 135 mgKOH / g, from the viewpoints of suppressing powdering after curing and maintaining low viscosity.
[0021] The anionic dispersant (A) is a compound containing an anionic group used as a dispersant, and is not particularly limited as long as the OH value is 40 mgKOH / g to 160 mgKOH / g. Examples of the anionic group contained in the anionic dispersant (A) include an acid group and its salt. Examples of the acid group include a carboxy group, a sulfo group, a phosphoric acid group, and a phosphonic acid group. From the viewpoint of suppressing powdering after curing and maintaining a low viscosity, the acid group is preferably a carboxy group or a phosphoric acid group. As the salt of the acid group, an alkali metal salt is preferred, and a sodium salt or potassium salt is more preferred. From the viewpoint of suppressing powdering after curing and maintaining a low viscosity, the anionic dispersant (A) is preferably a compound containing an acid group and a salt thereof, and more preferably a compound containing a carboxy group or a phosphate group and a salt thereof.
[0022] Examples of compounds containing a phosphate group or a salt thereof include alkyl phosphates (eg, sodium stearyl phosphate), alkyl ether phosphates (eg, polyoxyethylene oleyl ether phosphate, and polyoxyethylene stearyl ether phosphate), and the like. Of these, from the viewpoints of suppressing powdering after curing and maintaining a low viscosity, alkyl ether phosphates and salts thereof are preferred, and polyoxyalkylene alkyl ether phosphates and salts thereof are more preferred.
[0023] The alkyl ether phosphates and salts thereof and polyoxyalkylene alkyl ether phosphates and salts thereof preferably have an alkyl group having 6 to 40 carbon atoms, more preferably an alkyl group having 8 to 30 carbon atoms, and even more preferably an aliphatic hydrocarbon group having 12 to 20 carbon atoms.
[0024] The polyoxyalkylene group in the polyoxyalkylene alkyl ether phosphate and its salt may be, for example, a polyoxyethylene group, a polyoxypropylene group, a polyoxybutylene group, or a group in which these are randomly bonded. Among these, the polyoxyalkylene group is preferably a polyoxyethylene (POE) group.
[0025] From the viewpoint of suppressing powdering after curing and maintaining low viscosity, the compound containing a phosphate group or a salt thereof is preferably an alkyl ether phosphate having an alkyl group of 6 to 40 carbon atoms (preferably an alkyl group having 8 to 30 carbon atoms, more preferably an aliphatic hydrocarbon group having 12 to 20 carbon atoms) and a salt thereof, or a polyoxyalkylene alkyl ether phosphate and a salt thereof, more preferably a polyoxyalkylene alkyl ether phosphate having an alkyl group of 6 to 40 carbon atoms (preferably an alkyl group having 8 to 30 carbon atoms, more preferably an aliphatic hydrocarbon group having 12 to 20 carbon atoms) and a salt thereof, even more preferably a polyoxyethylene alkyl ether phosphate having an alkyl group of 6 to 40 carbon atoms (preferably an alkyl group having 8 to 30 carbon atoms, more preferably an aliphatic hydrocarbon group having 12 to 20 carbon atoms) and a salt thereof, and particularly preferably a polyoxyethylene oleyl ether phosphate and a salt thereof.
[0026] The compound containing a carboxy group or a salt thereof is not particularly limited, and may be a fatty acid having one carboxy group and a hydrocarbon group in one molecule and a salt thereof, or a compound having two or more carboxy groups in one molecule (hereinafter also referred to as a polycarboxylic acid) and a salt thereof. However, from the viewpoint of suppressing powdering after curing and maintaining low viscosity, a polycarboxylic acid and a salt thereof are preferred.
[0027] The polycarboxylic acid is not particularly limited, and examples thereof include aromatic polycarboxylic acids and aliphatic polycarboxylic acids. Examples of aromatic polycarboxylic acids include phthalic acid, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, tetrahydroisophthalic acid, hexahydrophthalic acid, hexahydroterephthalic acid, trimellitic acid, and pyromellitic acid. Examples of the aliphatic polycarboxylic acid include adipic acid, sebacic acid, succinic acid, azelaic acid, fumaric acid, maleic acid, and itaconic acid.
[0028] Examples of the polycarboxylate include alkylamine salts of polycarboxylates, alkylammonium salts, polyaminoamide polycarboxylates, sodium salts of polycarboxylates, ammonium salts of polycarboxylates, and aminoalcohol salts of polycarboxylates.
[0029] The polycarboxylic acid and its salt may be a polycarboxylic acid copolymer. The polycarboxylic acid copolymer may also be a comb polymer, which refers to a polymer having three or more side chains bonded to a main chain. In this specification, the main chain of a polymer refers to a portion extended by a reaction between polymerizable unsaturated groups, and the side chain of a polymer refers to a chain bonded to the main chain of the polymer.
[0030] From the viewpoint of suppressing powdering after curing and maintaining a low viscosity, the polycarboxylic acid-based copolymer preferably contains a structural unit formed from a polycarboxylic acid or a salt thereof and a structural unit formed from a steric repulsive group. It is presumed that by having the above-mentioned structural unit, the polycarboxylic acid or its salt portion is adsorbed to the thermally conductive filler, and the thermally conductive filler is dispersed by the steric repulsive force caused by the adsorption and the steric repulsive groups, thereby providing excellent suppression of powdering after curing.
[0031] Examples of the steric repulsive group include a polyether chain, a polyester chain, a polyamide chain, and an acrylic resin chain. Among these, it is more preferable that the steric repulsive group has a polyether chain, a polyester chain, or an acrylic resin chain, even more preferable that it has a polyether chain or an acrylic resin chain, and it is particularly preferable that it has a polyalkyleneoxy group as the polyether chain. Examples of the polyalkyleneoxy group include -(C2H4O)a- (a: an integer of 2 to 10) and -(C3H6O)a- (a: an integer of 2 to 10).
[0032] From the viewpoint of being more effective in suppressing powdering after curing, the structural unit formed from a polycarboxylic acid or a salt thereof is preferably a structural unit represented by the following formula (Pc1) or formula (Pc2).
[0033] [ka]
[0034] In formula (Pc1), R UA represents a hydrogen atom or a methyl group, and M represents a hydrogen atom or a cationic group. Examples of the cationic group include alkali metals such as sodium and calcium, and ammonium.
[0035] From the viewpoint of suppressing powdering after curing and maintaining low viscosity, the polycarboxylic acid-based copolymer is preferably a polycarboxylic acid-based copolymer containing, in its molecular structure, a structural unit formed from a carboxylic acid or a salt thereof and a structural unit formed from a steric repulsive group, and is more preferably a polymer having a structure represented by the following formula (Pc3).
[0036] [ka]
[0037] In formula (Pc3), R represents a hydrogen atom or a methyl group, M represents a hydrogen atom or an alkali metal, and m and n represent integers of 1 to 20.
[0038] The polycarboxylic acid copolymer may further contain structural units other than the structural units formed from the above carboxylic acids and their salts and the structural units formed from steric repulsive groups (hereinafter also referred to as "other structural units"). Other structural units include styrene.
[0039] The polycarboxylic acid copolymer may be a synthetic product or a commercially available product, such as Hypermer (registered trademark) KD-9 (a comb-shaped polymeric ionic dispersant having a polycarboxylic acid as the main skeleton and a hydrocarbon chain as a side chain, a weight average molecular weight of 760, and an acid value of 74 mgKOH / g) manufactured by CRODA.
[0040] The molecular weight of the anionic dispersant (when the molecular weight has a distribution, the weight average molecular weight) is not particularly limited, but is preferably less than 1,000, and more preferably 50 or more and 800 or less.
[0041] From the viewpoints of suppressing powdering after curing and maintaining low viscosity, the content of the anionic dispersant (A) is preferably 0.15 mass % to 0.8 mass %, more preferably 0.2 mass % to 0.6 mass %, and even more preferably 0.4 mass % to 0.6 mass %, relative to the total mass of the composition.
[0042] From the viewpoints of suppressing powdering after curing and maintaining low viscosity, the ratio of the content of the anionic dispersant (A) to the thermally conductive filler (F) described below (anionic dispersant (A) / thermally conductive filler (F)) is preferably 0.001 to 0.015 by mass, more preferably 0.002 to 0.01, and even more preferably 0.003 to 0.007. The anionic dispersant may be contained in the composition either alone or in combination of two or more kinds.
[0043] <Monomer (B) Having a (Meth)acryloyl Group> The curable composition according to the present disclosure includes a monomer (B) having a (meth)acryloyl group. The monomer (B) having a (meth)acryloyl group may be a monomer having one (meth)acrylate group in one molecule, or may be a monomer having two or more (meth)acrylate groups in one molecule. The monomer having one (meth)acrylate group in one molecule is not particularly limited, and examples thereof include linear, branched or cyclic alkyl (meth)acrylates, acrylic acid and the like. From the viewpoint of achieving both heat resistance and flexibility, the monomer having one (meth)acrylate group in one molecule is preferably a linear or branched alkyl (meth)acrylate, and more preferably contains a compound represented by the following formula (1).
[0044] [ka]
[0045] In formula (1), R 1 represents an alkyl group having 1 to 50 carbon atoms, R 2 represents a hydrogen atom or a methyl group.
[0046] In formula (1), R 1 The alkyl group in may be linear or branched, and may have a substituent. Examples of the substituent include a carboxy group, a hydroxy group, an amino group, an aryl group, and a heterocyclic group. A carboxy group or a hydroxy group is preferable, and a hydroxy group is more preferable.
[0047] From the viewpoint of achieving both heat resistance and flexibility, R 1 The alkyl group in the formula (I) preferably has 2 to 30 carbon atoms in total, more preferably 5 to 25 carbon atoms, further preferably 10 to 25 carbon atoms, and particularly preferably has 12 to 24 carbon atoms in total. Here, when the alkyl group has a substituent containing a carbon atom, the total number of carbon atoms means the total number of carbon atoms including the number of carbon atoms of the substituent.
[0048] From the viewpoint of achieving both heat resistance and flexibility, R 1 is preferably a linear or branched alkyl group or a substituted alkyl group having a total of 2 to 30 carbon atoms, more preferably a linear or branched alkyl group or a hydroxyl group having a total of 2 to 25 carbon atoms, and is preferably a linear or branched unsubstituted alkyl group having 12 to 24 carbon atoms.
[0049] Examples of monomers having one (meth)acrylate group in one molecule include lauryl (meth)acrylate, isostearyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 2-decyltetradecyl (meth)acrylate.
[0050] R 2 is a hydrogen atom or a methyl group, and is preferably a methyl group.
[0051] Examples of monomers having two or more (meth)acrylate groups in one molecule include hexanediol di(meth)acrylate, butanediol di(meth)acrylate (1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate), ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and trimethylolpropane tri(meth)acrylate.
[0052] From the viewpoint of achieving both heat resistance and flexibility, the monomer having two or more (meth)acrylate groups in one molecule is preferably a compound having two and / or three (meth)acrylate groups in one molecule, more preferably a compound having two (meth)acrylate groups in one molecule, and even more preferably a compound represented by the following formula (2).
[0053] [ka]
[0054] In formula (2), R B1 represents an alkylene group having 1 to 5 carbon atoms, R B2 and R B3 each independently represents a hydrogen atom or a methyl group, and n represents an integer of 4 or greater. R B1 The alkylene group having 1 to 5 carbon atoms represented by the following formula may be linear or branched. From a flexibility perspective, R B1 The alkylene group represented by the formula (I) is preferably a branched alkylene group having 2 to 5 carbon atoms, more preferably a linear or branched alkylene group having 2 to 4 carbon atoms, and even more preferably a branched alkylene group having 3 or 4 carbon atoms. R B2 and R B3 is preferably each independently a methyl group. n is preferably 4-25, more preferably 4-10, and further preferably 3-8.
[0055] From the viewpoint of flexibility and shape stability, R B1 is a branched alkylene group having 2 to 5 carbon atoms (more preferably a linear or branched alkylene group having 2 to 4 carbon atoms, and even more preferably a branched alkylene group having 3 or 4 carbon atoms), R B2 and R B3is a methyl group, and n is preferably 4 to 25 (more preferably 4 to 10, and further preferably 3 to 8).
[0056] In one embodiment, the monomer (B) having a (meth)acryloyl group preferably includes at least one selected from monomers having one (meth)acrylate group in one molecule, and at least one selected from monomers having two or more (meth)acrylate groups in one molecule.
[0057] The content ratio (A:B) of the content A of the monomer having one (meth)acrylate group in one molecule to the content B of the monomer having two or more (meth)acrylate groups in one molecule is preferably 99.5:0.5 to 95:5, and more preferably 99:1 to 97:3, from the viewpoints of the hardness and curing rate of the cured product.
[0058] The content of the monomer (B) having a (meth)acryloyl group is preferably from 1 to 10% by mass, and more preferably from 2 to 8% by mass, based on the total mass of the composition. The (meth)acryloyl group-containing monomer (B) may be contained in the composition either alone or in combination of two or more kinds.
[0059] The monomer (B) having a (meth)acryloyl group is preferably a monomer having a molecular weight of less than 1,000. In this specification, a monomer refers to a polymerizable compound having a molecular weight of less than 1,000, and a polymerizable polymer refers to a polymerizable compound having a weight average molecular weight (Mw) of 1,000 or more. The concept of "polymerizable polymer" in the present disclosure also includes so-called oligomers.
[0060] <Polymerization initiator (D)> The curable composition according to the present disclosure contains a polymerization initiator (D). The polymerization initiator (D) is a compound that generates polymerization initiating species such as radicals and cations by the energy of light, heat or both, and can be appropriately selected from known thermal polymerization initiators, known photopolymerization initiators, etc. As the polymerization initiator (D), from the viewpoint of the reactivity of the monomer (B) having a (meth)acryloyl group, a radical polymerization initiator is preferable, a peroxide that generates free radicals by heat is more preferable, and an organic peroxide that generates free radicals by heat is even more preferable.
[0061] The organic peroxides include isobutyl peroxide, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, di-n-propyl peroxydicarbonate, di-s-butyl peroxydicarbonate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, di-2-ethoxyethyl peroxydicarbonate, and di(ethylhexyl)peroxy. Dicarbonate, t-hexyl peroxyneodecanoate, dimethoxybutyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxydicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, succinic peroxide, 2,5-dimethyl-2,5-di (2-ethylhexanoyl)hexane, 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate, t-hexylperoxy-2-ethylhexanoate, 4-methylbenzoyl peroxide, t-butylperoxy-2-ethylhexanoate, m-toluenebenzoyl peroxide, benzoyl peroxide, t-butylperoxyisobutyrate, 1,1-bis(t-butylperoxy)2-methylcyclohexane, 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1 -Bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexanone, 2,2-bis(4,4-dibutylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)cyclododecane, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5-dimethyl-2,5-di(m-toluoylperoxy)hexane, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl carbonate, t-hexylperoxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxyacetate, 2,2-bis(t-butylperoxy)butane, t-butylperoxybenzoate, n-butyl-4,4-bis(t-butylperoxy)valerate, di-t-butylperoxyisophthalate, α,α'-bis(t-butylperoxy)diisopropylbenzene, dicumylperoxy Examples of peroxides include 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-butyl peroxide, p-menthane hydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, diisopropylbenzene hydroperoxide, t-butyltrimethylsilyl peroxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, t-hexyl hydroperoxide, t-butyl hydroperoxide, benzoyl peroxide, and lauroyl peroxide. Among these, from the viewpoint of reactivity, the organic peroxide is preferably at least one compound selected from the group consisting of benzoyl peroxide, t-butylperoxy-2-ethylhexyl carbonate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, and cumene hydroperoxide.
[0062] -Content- The content of the polymerization initiator (D) is preferably 0.5 parts by mass or more and 10 parts by mass or less, and more preferably 0.5 parts by mass or more and 4 parts by mass or less, based on 100 parts by mass of the monomer (B) having a (meth)acryloyl group.
[0063] <Thermal conductive filler (F)> The curable composition according to the present disclosure comprises a thermally conductive filler (F). The material of the thermally conductive filler (F) is not particularly limited, and examples thereof include zinc oxide, magnesium oxide, aluminum oxide, boron nitride, aluminum nitride, carbon, etc. From the viewpoint of high thermal conductivity and excellent insulation properties, it is preferable to include at least one selected from zinc oxide, magnesium oxide, and aluminum oxide, and it is more preferable to include zinc oxide. The zinc oxide, magnesium oxide and aluminum oxide used as the thermally conductive filler are not particularly limited, and examples thereof include zinc oxide that is commonly used as a thermally conductive filler.
[0064] The thermally conductive filler (F) may be a surface-treated thermally conductive filler. The inclusion of a surface-treated thermally conductive filler improves the affinity between the thermally conductive filler and other components contained other than the thermally conductive filler, and can contribute to suppressing powdering after curing and improving the maintenance of low viscosity.
[0065] The surface treatment of the thermally conductive filler is not particularly limited and may be a physical treatment or a chemical treatment, and any known treatment capable of treating the surfaces of the particles constituting the thermally conductive filler can be applied. The surface treatment is preferably a treatment using a surface treatment agent.
[0066] Examples of the surface treatment agent include a silane-based coupling agent, a titanium-based coupling agent, a carboxylic acid-based coupling agent, a phosphoric acid-based coupling agent, a fatty acid, a polymer compound, a surfactant, and a fat or oil.
[0067] From the viewpoint of dispersibility, the thermally conductive filler (F) is preferably surface-treated with a silane coupling agent as a surface treatment agent.
[0068] The thermally conductive filler (F) may be a thermally conductive filler that has been entirely surface-treated, or may be a thermally conductive filler that has been partially surface-treated. From the viewpoints of suppressing powdering after curing, maintaining low viscosity, and achieving high thermal conductivity, it is preferable that the thermally conductive filler (F) contains a thermally conductive filler that has been surface-treated.
[0069] From the viewpoints of suppressing powdering after curing, maintaining low viscosity, and thermal conductivity, the thermal conductive filler (F) preferably has a volume average particle size of 0.05 μm to 30 μm, more preferably 0.1 μm to 20 μm, and even more preferably 0.3 μm to 15 μm.
[0070] In addition, in order to achieve superior thermal conductivity, suppress powdering after curing, and maintain low viscosity, a thermally conductive filler (F) (preferably zinc oxide) having a volume average particle diameter of more than 30 μm may be used in combination with a thermally conductive filler (F) having a volume average particle diameter of 0.05 μm to 30 μm (preferably 0.1 μm to 20 μm, and more preferably 0.1 μm to 15 μm), or a thermally conductive filler (F) having a volume average particle diameter of more than 30 μm and not more than 50 μm may be used in combination.
[0071] The volume average particle size of the thermally conductive filler is measured by a laser diffraction / scattering method in accordance with JIS Z 8825:2013 (corresponding international standard: ISO13320). Specifically, a laser diffraction / scattering particle size analyzer is used to measure the volume distribution of the thermally conductive filler particles in a sample containing the thermally conductive filler particles. Based on the measured value (volume distribution) thus obtained, the volume average particle size of the thermally conductive filler particles contained in the sample can be calculated. As an example of the measuring device, a laser diffraction scattering type particle size measuring device, product name: Nanoparticle Size Distribution Measuring Device SALD-7500nano, manufactured by Shimadzu Corporation, can be used.
[0072] In the curable composition according to the present disclosure, from the viewpoint of highly loading the thermally conductive filler (F) in the composition, it is preferable to contain two or more types of thermally conductive fillers (F) (preferably zinc oxide) having different volume average particle sizes. When the curable composition according to the present disclosure contains two or more types of thermally conductive fillers (F) (preferably zinc oxide) having different volume average particle diameters, from the above viewpoint, it is preferable that the ratio of the maximum volume average particle diameter to the minimum volume average particle diameter is 1.5 or more.
[0073] In addition, in the curable composition according to the present disclosure, in terms of achieving superior thermal conductivity, suppression of powdering after curing, and maintenance of low viscosity, it is more preferable that the curable composition contains two or more types of zinc oxide having a volume average particle diameter of 0.05 μm to 30 μm, a difference in volume average particle diameter of 5 μm or more, and different volume average particle diameters.
[0074] -Content- The content of the thermally conductive filler (F) is preferably 80 mass % or more, more preferably 85 mass % to 98 mass %, and even more preferably 90 mass % to 96 mass %, based on the total mass of the composition.
[0075] The content of the thermally conductive filler (F) other than zinc oxide is preferably 60 mass % or less, more preferably 40 mass % or less, and even more preferably 0 mass % or more and 20 mass % or less, based on the total mass of the thermally conductive filler (F) and the total mass of the composition.
[0076] <Plasticizer (E)> The curable composition according to the present disclosure comprises a plasticizer (E). The plasticizer (E) is not particularly limited, and examples thereof include polymers used as plasticizers, fatty acid ester compounds having an unsaturated hydrocarbon group, aromatic carboxylic acid ester compounds, and oils containing fatty acids and aromatic carboxylic acids having an unsaturated hydrocarbon group. In this disclosure, "polymer" refers to a compound having a weight average molecular weight (Mw) of 1,000 or more. In the present disclosure, the concept of "polymer" also includes so-called oligomers.
[0077] Examples of polymers used as plasticizers include acrylic polymers, polyester polymers, polyurethane polymers, and silicone polymers. From the viewpoints of maintaining a low viscosity, suppressing powdering after curing, heat resistance, and flexibility after curing, acrylic polymers are preferred.
[0078] The acrylic polymer is not particularly limited as long as it is a polymer having a structural unit formed from an acrylic monomer, and the acrylic polymer may be a homopolymer or a copolymer. Examples of the acrylic monomer include acrylic acid, acrylic esters, acrylonitrile, acrylamide, and methylol acrylamide.
[0079] The acrylic polymer preferably contains a structural unit formed from an acrylic ester from the viewpoints of maintaining a low viscosity and heat resistance. The (meth)acrylic ester is preferably an alkyl (meth)acrylate. Examples of the meth)acrylic ester include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and isobutyl (meth)acrylate. The alkyl acrylate may be a non-functional alkyl acrylate, or may have a functional group such as a carboxy group or a hydroxy group (hydroxyl group).
[0080] The acrylic polymer is represented by the following formula (P AC It is preferable that the polymer has a structure represented by the following formula:
[0081] [ka]
[0082] Formula (P ACIn the above, Rp represents a hydrogen atom or an alkyl group. Formula (P AC In the above, the alkyl group may have a substituent. Examples of the substituent include a carboxy group, a hydroxyl group, and an amino group. The substituent is preferably a carboxy group or a hydroxy group, and more preferably a hydroxy group. The alkyl group is preferably a saturated alkyl group, more preferably an alkyl group having 1 to 4 carbon atoms.
[0083] When the curable composition according to the present disclosure contains a plasticizer (E) and the plasticizer (E) is a polymer, the plasticizer (E) is preferably a polymer having a glass transition temperature of −20° C. or lower, and more preferably an acrylic polymer having a glass transition temperature of −20° C. or lower. The glass transition temperature (Tg) of a polymer can be determined by examining the inflection point of a DSC curve measured using a differential scanning calorimeter (DSC).
[0084] Examples of fatty acid ester compounds having an unsaturated hydrocarbon group include ester compounds of palmitoleic acid, oleic acid, linoleic acid, linolenic acid, and the like. Examples of the aromatic carboxylate compound include ester compounds of phthalic acid, terephthalic acid, benzoic acid, trimellitic acid, and the like.
[0085] When the curable composition according to the present disclosure contains a plasticizer (E), from the viewpoints of maintaining a low viscosity and high-temperature stability, the plasticizer (E) preferably contains at least one compound selected from the group consisting of an acrylic polymer and an aromatic carboxylate compound, and is represented by the formula (P AC It is more preferable that the polymer contains at least one compound selected from the group consisting of a polymer having a structure represented by the following formula (I):
[0086] -Content- When the curable composition according to the present disclosure contains a plasticizer (E) (the total amount when two or more types are contained), from the viewpoint of maintaining a low viscosity and simultaneously achieving heat resistance and flexibility, the content of the plasticizer (E) is preferably 10 parts by mass to 60 parts by mass, more preferably 20 parts by mass to 50 parts by mass, and even more preferably 30 parts by mass to 45 parts by mass, relative to 100 parts by mass of the monomer (B) having a (meth)acryloyl group. The plasticizer (E) may be contained in the composition either alone or in combination of two or more kinds.
[0087] <<Other additives>> The curable composition according to the present disclosure may contain components other than the anionic dispersant (A), the monomer (B) having a (meth)acryloyl group, the polymerization initiator (D), the thermally conductive filler (F), and the plasticizer (E) (hereinafter also referred to as “other additives”), as necessary. Other additives that may be appropriately blended include other dispersants, reducing agents (G), antioxidants, corrosion inhibitors, rust inhibitors, and rheology control agents (viscosity modifiers). The above additives may be used alone or in combination of two or more. <<Reducing Agent (G)>> The curable composition according to the present disclosure may further contain a reducing agent (G) as necessary. When the curable composition according to the present disclosure is applied to a two-part curable composition described later, it is preferable that one of the curable compositions contains the reducing agent (G). The addition of the reducing agent (G) facilitates the decomposition of the polymerization initiator (D) (for example, a peroxide), and the polymerization reaction easily proceeds even under low temperature conditions.
[0088] The reducing agent (G) is not particularly limited as long as it can promote the decomposition of the above-mentioned polymerization initiator (D), and examples thereof include known reducing agents that are used in combination with polymerization initiators. From the viewpoint of promoting the decomposition of the polymerization initiator (D), a metal compound-based reducing agent is preferable.
[0089] Examples of metal compound reducing agents include stannous oxide, dioctyltin dilaurate, dibutyltin dilaurate, dibutyltin diacetate, zinc naphthenate, antimony trichloride, potassium oleate, sodium O-phenylphenate, bismuth nitrate, ferric chloride, tetra-n-butyltin, tetra(2-ethylhexyl) titanate, cobalt 2-ethylhexoate, and ferric 2-ethylhexoate. Among these, from the viewpoint of reactivity, cobalt 2-ethylhexoate and cobalt naphthenate are preferred as the metal compound reducing agent.
[0090] -Content- When the curable composition according to the present disclosure contains a reducing agent (G), from the viewpoint of the curing rate, the content of the reducing agent (G) is preferably 0.5 parts by mass or more and 10 parts by mass or less, and more preferably 2 parts by mass or more and 9 parts by mass or less, relative to 100 parts by mass of the monomer (B) having a (meth)acryloyl group. The reducing agent (F) may be used alone or in combination of two or more kinds.
[0091] <<Other dispersants>> The curable composition according to the present disclosure may further contain a dispersant other than the anionic dispersant (A) (hereinafter, may also be referred to as "other dispersants"). The other dispersants are not particularly limited as long as they are dispersants other than the anionic dispersant (A), and examples thereof include cationic surfactants, nonionic surfactants, amphoteric surfactants, polymeric surfactants, alcohols, metal soaps, fluorine-based surfactants, and boron-based surfactants.
[0092] The content of the other dispersant is preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 0 mass% or more and 1 mass% or less, relative to the total mass of the dispersant contained in the curable composition according to the present disclosure, and it is particularly preferable that no other dispersant is contained.
[0093] <<Antioxidants>> Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, and phosphite-based antioxidants.
[0094] <<Corrosion inhibitor>> Corrosion inhibitors include benzotriazole, tolyltriazole, thiadiazole, benzimidazole, and the like.
[0095] <<Rust inhibitor>> Examples of the rust inhibitor include metal sulfonate compounds and sorbitan compounds.
[0096] <<Rheology control agent>> In the present disclosure, a rheology control agent refers to an additive that imparts non-Newtonian properties to changes in shear rate, and imparts flow characteristics such as increasing the shear viscosity in the low shear rate range while decreasing the shear viscosity in the high shear rate range.
[0097] The rheology control agent may be an inorganic compound-based rheology control agent or an organic compound-based rheology control agent. Examples of inorganic compound-based rheology control agents include fumed silica, bentonite, mica, and kaolin. Examples of the organic compound-based rheology control agent include urea-modified polymers, urethane-modified polymers, castor oil wax, polyethylene wax, polyamide wax, and fatty acid amide wax. Among these, the rheology control agent is preferably an inorganic compound-based rheology control agent, more preferably fumed silica or bentonite, and even more preferably bentonite. When using fumed silica, it is preferable to use one whose surface is made hydrophobic by a silane coupling agent or other surface modifier. When using bentonite, it is preferable to use an organically modified bentonite that is organically modified by a quaternary ammonium salt or other organic modifier.
[0098] The content of the rheology control agent is not particularly limited and can be set appropriately.
[0099] [Physical Properties of Curable Composition] The spreading consistency of the curable composition according to the present disclosure is preferably 100 to 500, more preferably 260 to 340, and even more preferably 280 to 310, from the viewpoints of viscoelasticity, handleability, and defoaming properties. The spreading consistency is calculated by inserting 0.05 mL of a sample (curable composition before curing) between two acrylic plates in an environment of 25°C, compressing the sample by applying a load of 100 g on the plates for 5 seconds, measuring the spreading diameter of the sample in millimeters, subtracting 1 from this measurement and multiplying the result by 20. Spreading consistency = (measured value - 1) x 20
[0100] [Form of the curable composition] The curable composition according to the present disclosure is preferably a one-part curable composition in which one type of curable composition is used when applying to a substrate, a heating element, etc. The curable composition according to the present disclosure may be a two-part curable composition in which two types of curable compositions are mixed and used.
[0101] [Method for producing curable composition] The method for producing the curable composition according to the present disclosure is not particularly limited, and is not particularly limited. The curable composition according to the present disclosure can be produced, for example, by the following method. The anionic dispersant (A), the monomer having a (meth)acryloyl group (B), the polymerization initiator (D), the plasticizer (E), the thermally conductive filler (F), and other additives as required are placed in a stirring vessel and stirred and mixed to obtain the composition. For stirring and mixing, a known stirrer or the like can be used.
[0102] In the method for producing a curable composition, when other additives are added, the additives may be stirred for a period of time that allows the additives to be dissolved or dispersed. The additives may be added to a stirring vessel together with the anionic dispersant (A), the monomer (B) having a (meth)acryloyl group, the polymerization initiator (D), the plasticizer (E) and the thermally conductive filler (F), or may be added after mixing of components other than the other additives.
[0103] (cured product) The cured product according to the present disclosure is a cured product of the curable composition according to the present disclosure. The method for curing the curable composition is not limited and can be appropriately selected from commonly used methods. The curing method includes irradiation with active energy rays, heating, etc., and the curing method by heating is preferred. When curing is performed by heating, the heating temperature is preferably 60° C. or higher, and more preferably 70° C. or higher. The heating time is preferably 1 minute to 120 minutes. The curable composition may be cured by reacting with moisture in the air, or may be cured at room temperature.
[0104] From the viewpoints of flexibility, shape stability, and suppression of changes in thermal conductivity, the thermal conductivity of the cured product according to the present disclosure is preferably 0.5 (W·m / K) to 50 (W·m / K), preferably 1 (W·m / K) to 20 (W·m / K), and more preferably 3 (W·m / K) to 20 (W·m / K). The softness of the cured product according to the present disclosure is preferably 100 or less, and more preferably 85 or less, in Shore OO, from the viewpoint of stress relaxation to peripheral parts of the cured product. Similarly, the Asker C hardness is preferably 100 or less, more preferably 85 or less, and even more preferably 75 or less. The softness of the cured product according to the present disclosure is determined in accordance with ASTM D2240, and Asker C is determined in accordance with JIS K 7312 (1996).
[0105] <Application> The curable composition according to the present disclosure can be suitably used, for example, as a TIM that is filled in a recess (a gap between a heat generating element and a heat sink) formed in a substrate. The curable composition according to the present disclosure is excellent in suppressing powdering after curing, and therefore can maintain the desired quality for a long period of time. In addition, the curable composition according to the present disclosure is excellent in manufacturability and thermal conductivity of the obtained cured product, because of its low viscosity and excellent thermal conductivity. The cured product obtained from the curable composition according to the present disclosure has excellent flexibility, shape stability, and thermal conductivity, and therefore has excellent conformability to the coated surface such as a recess formed on a substrate, and therefore can efficiently release heat even when there are components of different heights on the substrate. In addition, the curable composition according to the present disclosure can efficiently release heat because it can conform to the microscopic unevenness of the material on the substrate, and also has excellent conformability to the coated surface due to temperature fluctuations, and therefore can be suitably used as a gap filler. EXAMPLES
[0106] The curable composition and the cured product according to the present disclosure will be specifically described below with reference to examples. Note that the curable composition and the cured product according to the present disclosure are not limited to these examples in any way.
[0107] (Examples 1 to 10 and Comparative Examples 1 to 9) The raw materials were mixed in the amounts shown in Tables 1 and 2 and mixed at 2,000 rpm (revolutions per minute) for 2 minutes under atmospheric pressure using a planetary centrifugal mixer (Thinky Corporation, product name: Awatori Rentaro ARV-310) to prepare a curable composition.
[0108] Example 11 The raw materials for liquid A and liquid B were mixed in the amounts shown in Table 1 and mixed at 2,000 rpm for 2 minutes under atmospheric pressure using a planetary centrifugal mixer (Thinky Corporation, product name: Awatori Rentaro ARV-310) to obtain liquid A and liquid B. Liquid A and B were then mixed in a mass ratio of 1:1 and mixed at 2,000 rpm for 1 minute under atmospheric pressure using a planetary centrifugal mixer (Thinky Corporation, product name: Awatori Rentaro ARV-310) to prepare a two-part curable composition.
[0109] The following evaluations were carried out using the curable compositions prepared in Examples 1 to 11 and Comparative Examples 1 to 9. The results are shown in Tables 1 and 2.
[0110] -evaluation- <Viscosity (maintaining low viscosity)> The shear viscosity η [Pa·s] of the curable composition prepared above at 25° C. was measured using a dynamic viscoelasticity measuring device (manufactured by Anton Paar, product name: MCR 101). A PP25 parallel plate (diameter 25 mm, manufactured by Anton Paar) was used as a jig for the curable composition to be measured. The measurements were performed by measuring the shear viscosity η [Pa s] at shear rates of 0.01 [1 / s], 0.1 [1 / s], 1 [1 / s], 10 [1 / s] and 100 [1 / s]. A material can be said to be excellent at maintaining low viscosity when its shear viscosity η [Pa s] at 25°C, measured at a shear rate of 0.1 [1 / s], is 100 [Pa s] or less.
[0111] <Powdering> The curable composition prepared above was cured at 80° C. for 30 minutes in a N2 purged atmosphere, and the cured product was molded to have dimensions of 30 mm length x 10 mm width x height (thickness) x 6 mm. The molded cured product was subjected to a repeated bending test. The vertical end of the cured product was grasped, and this end was bent up and down at an angle of 5 degrees or more from the vertical direction of the cured product, and the series of movements up to returning the end to its original state was counted as one round trip. After carrying out this movement 100 times, the mass of components that had peeled off from the cured product was measured, and the suppression of powdering after curing was evaluated based on the following evaluation criteria. When the dusting rating is A, it can be said that the material is excellent at suppressing dusting after curing. -Evaluation criteria- A: No powdering is observed. B: The mass of the powdered components is within 0.05 mass% of the total mass. C: The mass of powdery components is 0.05 mass% or more of the total mass.
[0112] <Thermal conductivity (W / (m K)> Thermal conductivity was measured according to ASTM D5470. The curable composition was molded to have dimensions of 10 mm x 10 mm x 1.0 mm (length x width x height (thickness)), sandwiched between 10 mm x 10 mm copper plates, and cured at 80°C for 30 minutes in a N2 purged atmosphere. The thermal resistance (unit: K cm) was then measured using a thermal resistance measuring device (Tsukubarika Seiki Co., Ltd., product name: thermal resistance measuring device). 2 / W) was measured and converted into thermal conductivity.
[0113] <Spreading consistency> The spreading consistency was determined by inserting 0.05 mL of a sample (curable composition before curing) between two acrylic plates in an environment of 25°C, compressing the sample by applying a load of 100 g on the plates for 5 seconds, measuring the spreading diameter of the sample in millimeters, subtracting 1 from this measurement and multiplying the result by 20.
[0114] <Hardness: shape stability> -Softness after curing: Shore OO hardness (sample thickness: 6 mm)- The softness of the cured product of the curable composition was measured in accordance with ASTM D2240. The curable composition was molded into a size of 50 mm x 20 mm x 6 mm (thickness: 6 mm) and cured under a N2 purged atmosphere at 80°C for 30 minutes. The Shore OO hardness was then measured using a durometer (product name: GS-754G, manufactured by Techclock Corporation).
[0115] -Softness after hardening: Asker C hardness (sample thickness: 6 mm)- The softness of the cured product of the curable composition was measured in accordance with JIS K 7312 (1996). The curable composition was molded into a size of 50 mm x 20 mm x 6 mm (thickness 6 mm) and cured under a N2 purged atmosphere at 80°C for 30 minutes, after which the Asker C hardness was measured using an Asker rubber hardness tester Type C (manufactured by Kobunshi Keiki Co., Ltd.).
[0116] [Table 1]
[0117] [Table 2]
[0118] Details of each component listed in Tables 1 and 2 are as follows: "-" in Tables 1 and 2 indicates that the corresponding component is not included. In Tables 1 and 2, "filling ratio by mass [%]" represents the mass ratio of the total mass of the thermally conductive filler (F) to the total mass of the composition. In Tables 1 and 2, dispersant / filler represents the mass ratio of the anionic dispersant (A) to the total mass of the thermally conductive filler (F).
[0119] <<Monomer (B) Having a (Meth)acryloyl Group>> Light Ester L: Lauryl methacrylate; Kyoeisha Chemical Co., Ltd., product name: LMA HO-250(N): 2-hydroxyethyl methacrylate; manufactured by Kyoeisha Chemical Co., Ltd.; Product name: HO-250(N) ITEC: 2-Decyltetradecyl methacrylate; manufactured by Shin-Nakamura Chemical Co., Ltd. 9PG (bifunctional monomer): Polypropylene glycol dimethacrylate; manufactured by Shin-Nakamura Chemical Co., Ltd.; Product name: 9PG
[0120] <<Plasticizer (E)>> ARUFON UP-1020 (product name); acrylic polymer; manufactured by Toagosei Co., Ltd.; weight average molecular weight; 2,000; glass transition temperature (Tg); -80°C Adeka Cizer C-880 (product name); mixed linear alkyl trimellitate; manufactured by ADEKA Corporation;
[0121] <<Polymerization initiator (C)>> · Kayakumen H: Cumene hydroperoxide; manufactured by Kayaku Akzo Co., Ltd. Perocta O: 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate; NOF Corp.
[0122] <<Reducing Agent (G)>> Cobalt hexoate; manufactured by Toei Kako Co., Ltd.
[0123] <<Anionic dispersant (A)>> ·Crodafos O3A: Oxyethylene oleyl ether phosphate (anionic dispersant), OH value: 130 mg KOH / g, molecular weight: 420, manufactured by Croda Hypermer KD9: Comb-shaped polycarboxylic acid (anionic dispersant), weight average molecular weight 760, OH value 66mgKOH / g~77mgKOH / g, manufactured by CRODA Hypermer KD3: Comb-shaped polyamine (weak cationic polymer), weight average molecular weight: 2,000-30,000, OH value: 16mgKOH / g-25mgKOH / g, manufactured by CRODA Hypermer KD4: Comb-type polycarboxylic acid (weak anionic polymer), weight average molecular weight 1,700, OH value: 28 mgKOH / g, manufactured by CRODA Hypermer KD16: Dicarboxylic acid, weak anionic compound, manufactured by CRODA, molecular weight: 490, OH value: 299mgKOH / g, manufactured by CRODA Hypermer KD57: Dicarboxylic acid, weak anionic compound, manufactured by CRODA, molecular weight: 470, OH value: 489mgKOH / g, manufactured by CRODA Oleic acid (9-octadecenoic acid); molecular weight: 282, OH value: 198mgKOH / g~204mgKOH / g, NOF Corp. NIKKOL (registered trademark) Selakyl Alcohol (product name); monooleyl glyceryl ether, molecular weight: 342, OH value: 295 mg KOH / g to 335 mg KOH / g, manufactured by Nippon Surfactant Industries Co., Ltd.
[0124] <<Other additives>> Viscosity modifier (rheology control agent): CLAYTONE-40: BYK
[0125] <<Thermal conductive filler (F)>> Zinc oxide type 1; volume average diameter D50; 0.6 μm, manufactured by Sakai Chemical Industry Co., Ltd. Calcined zinc oxide; volume average diameter D50; 4μm, manufactured by Hakusui Tech Co., Ltd. Calcined zinc oxide (surface treatment product); treated with silane coupling agent; volume average particle size: 12 μm; manufactured by Hakusui Tech Co., Ltd.
[0126] As shown by the results in Tables 1 and 2, the cured products formed from the curable compositions of Examples 1 to 11 are superior in suppressing powdering after curing and maintaining low viscosity compared to the cured products formed from the curable compositions of Comparative Examples 1 to 9. From the above, the curable compositions and cured products according to the present disclosure can be suitably used as gap fillers.
Claims
1. An anionic dispersant (A) having an OH value of 40 mg KOH to 160 mg KOH / g; A monomer (B) having a (meth)acryloyl group; A polymerization initiator (D); A plasticizer (E); A thermally conductive filler (F); Including, The content of the anionic dispersant (A) is 0.1% by mass to 1.0% by mass based on the total mass of the composition, The curable composition, wherein the anionic dispersant (A) contains at least one selected from the group consisting of a compound containing a carboxy group and a compound containing a phosphate group.
2. The curable composition according to claim 1 , wherein the monomer (B) comprises a compound represented by the following formula (1): 【Chemistry 1】 In formula (1), R 1 represents an alkyl group having 1 to 50 carbon atoms; R 2 represents a hydrogen atom or a methyl group.
3. The curable composition according to claim 1 or 2, wherein the monomer (B) comprises a compound represented by the following formula (2): 【Chemistry 2】 In formula (2), R B1 represents an alkylene group having 1 to 5 carbon atoms; R B2 and R B3 each independently represents a hydrogen atom or a methyl group, and n represents an integer of 4 or greater.
4. The curable composition according to any one of claims 1 to 3, wherein the molecular weight of the anionic dispersant (A) is less than 1,000.
5. The curable composition according to any one of claims 1 to 4, wherein the plasticizer (E) comprises an acrylic polymer or a trimellitic acid ester.
6. The curable composition according to any one of claims 1 to 5, wherein a ratio of the content of the anionic dispersant (A) to the thermally conductive filler (F) (anionic dispersant (A) / thermally conductive filler (F)) is 0.001 to 0.015 on a mass basis.
7. The curable composition according to any one of claims 1 to 6, wherein the thermally conductive filler (F) comprises zinc oxide.
8. The curable composition according to any one of claims 1 to 7, wherein the content of the thermally conductive filler (F) is 70% by mass to 98% by mass based on the total mass of the composition.
9. A cured product of the curable composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Curable resin composition
JP2011052130A
Flame-retardant thermally-conductive composition and flame-retardant thermally-conductive sheet using the same
JP2011184644A
Thermally conductive molded article and its manufacturing method
JP2019119131A
Curable composition and cured material
WO2020149193A1